Free-standing microchamber arrays as a biodegradable drug depot system for implant coatings. (May 2019) - Zykova, Yulia; Kudryavtseva, Valeriya; Gai, Meiyu; Kozelskaya, Anna; Frueh, Johannes; Sukhorukov, Gleb; Tverdokhlebov, Sergei
Graphical abstract: Highlights: A PLLA microchamber arrays films are proposed to deliver water-soluble substances. Rhodamine B was completely released from PLLA microchambers in vitro within 13 days. Low frequency ultrasound damages and detaches PLLA microchambers. Free-standing microchamber arrays can be applied as endovascular stent cover. Abstract: The combination of an efficient encapsulation method of small water-soluble substances with a stimuli-responsive release of defined quantity remains a challenging task. A novel drug delivery system (DDS) representing a free-standing PLLA microchamber arrays film and its application as the cover for implantable endovascular stent are reported in this work. The proposed DDS preparation method is consisting of a patterned polydimethylsiloxane (PDMS)-stamp dip-coated into a polymer solution followed by drug loading and sealing it by polymer pre-coated substrate. It was shown that using 1 wt% PLLA solution is optimal for obtaining microchamber arrays with an individual cargo capacity of 2.88 × 10 −9 µg, which was successfully loaded by model drug substance Rhodamine B. Rhodamine B was completely released in vitro during 13 days in PBS at 37 °C by diffusion. It was demonstrated that low-frequency ultrasound (LFUS, 20 kHz) allows triggering RhB release due to microchamber damage and detachment of individual PLLA microchambers over time. LFUS exposure time up to 25 s led to RhB release of up to 8.4 × 10 −4 µg (approximately 55%) from microchambers located on the flat substrate; up to 5.2 × 10 −4 µg from microchambers located on the stent with using a simplified vessel model. Furthermore, the free-standing printed PLLA microchamber arrays were demonstrated to be applied as endovascular stent cover that can be used for complementary pharmacological effect, for example, triggered local delivery of anticoagulants.